Comparison of mechanistic pathways of bariatric surgery in patients with diabetes mellitus: A Bayesian network meta‐analysis. Issue 7 (17th June 2022) - Lin, Chaoxing; Yeong, Trevor James Jun‐Ming; Lim, Wen Hui; Ng, Cheng Han; Yau, Chun En; Chin, Yip Han; Muthiah, Mark D.; Loh, Poay Huan; Foo, Roger S. Y.; Mok, Shao Feng; Shabbir, Asim; Dimitriadis, Georgios K.; et al.
Abstract: Objective: Metabolic bariatric procedures are potentially efficacious treatment options in patients with type 2 diabetes mellitus (T2DM). Previous meta‐analyses focused on individual operative approaches rather than the mechanistic pathways behind different bariatric procedures. This updated network meta‐analysis aimed to synthesize new evidence and comparatively evaluate the efficacy of metabolic surgery against restrictive procedures and standard first‐line treatment for patients with T2DM. Methods: Embase, MEDLINE, and trial registries were searched for randomized controlled trials on bariatric surgeries in patients with T2DM on September 3, 2021. A Bayesian network meta‐analysis was conducted. The primary outcome was T2DM remission. Secondary outcomes included changes in BMI, lipoprotein levels, and blood pressure. Results: Thirty‐two articles were included. Metabolic surgery was statistically superior to restrictive procedures (risk ratio [RR]: 2.57, 95% credibility intervals [CrI]: 1.36‐5.43), medical therapy (RR: 35.29, 95% Crl: 10.56‐183.23), and lifestyle intervention (RR: 40.51, 95% Crl: 5.32‐402.59) in T2DM remission. Metabolic surgery significantly lowered BMI and blood pressure compared with other interventions. Restrictive procedures significantly increased high‐density lipoprotein compared with metabolic surgery. Lifestyle intervention and metabolic surgery were statistically superior to restrictive procedures in reducing low‐density lipoprotein. Conclusions: The superiority in diabetes remission and favorable metabolic profile support the choice of metabolic surgery over restrictive bariatric procedures.